Towards “just” energy transitions in unequal societies: an actor-centric analysis of South Africa's evolving electricity sector - Nkata, Zimkita (Department of Environmental and Geographical Science, 2023)
The rapid and intensifying impacts of the changing climate and subsequent need to alleviate these have resulted in the synonymous pathway towards a global energy transition. Through enhanced national climate action plans, countries worldwide are formulating development pathways that are aligned to a carbon-neutral and net-zero emissions global economy. The recent IPCC Sixth Assessment report confirmed, once again, the urgency to reduce emissions to prevent catastrophic climate impacts. While nations have submitted their enhanced climate action plans, developing countries like South Africa battle with severe developmental challenges. The imperative to respond to climate change alongside addressing entrenched development challenges such as high unemployment, inequality, and poverty make it essential for the country's energy transition to be just. Frameworks theorising technological transitions predominantly originate from the global north. Thus, to avoid adopting frameworks from their place of origin and replicating them in different contexts, this study merges Geel's multi-level perspective (MLP) framework with the energy justice framework to have a better understanding of the composition of actors and discourse shaping South Africa's just energy transition debate. The study achieves this by operationalizing a range of qualitative discursive approaches, namely content and media frame analysis. Over an 11-year study period, online newspaper articles are used as a unit of analysis to develop actor categories, these are accompanied by frames (in the form of statements said by the identified actors). With the assumption of there being no agency at the landscape level of the MLP, landscape developments placing pressure on the regime identified from the analysis include the climate change phenomenon, pressure from the international community, and declining global demand for coal. At the regime level, actors engaging in activities reinforcing the status quo such as Eskom and members of business fell within the incumbent (core) actor category whereas actors who were identified as outsiders (i.e., those that openly criticize the regime by highlighting problems associated with it) mainly consisted of civil society groups. Within each actor category, actors use discourse that either stabilizes or destabilizes the regime. At the niche level, the financial intermediary role played by development finance institutions (DFI's) emerged as key to creating protective spaces for the adoption of renewable energy technologies throughout the study period. Finally, because of the varying levels of power and interactions between actors across the multiple levels of the country's energy transition, issues of fairness in decision-making (procedural justice), representation (recognitional justice) and share in costs and benefits of the regime and transition emerge (distributive justice).